The Significant Role of Communication, Price, and Quality in Creating a Brand Trust to Achieve Purchase Behavior Antecedents and Consequence of Consumer Brand Trust - Jamal Mohammed Esmail Alekam; Nik Kamariah Nik Mat; Salniza Md. Salleh (International Journal of Supply Chain Management, 2017)
According to the relationship marketing factors, brand trust is one of the key element in brand building and in securing customer loyalty. Hence, the objective of this study is to examine the influence of product price, perceived product quality, and communication on brand trust and the effect of brand trust on consumer purchase behavior based on Relationship Theory perspective. The research instrument was developed based on items taken from previous studies. Questionnaires were distributed to 1000 consumers in 10 primary and secondary School in 3 city Sanaa, Ibb and Aden districts in Yemen. of the total distributed questionnaires, only 711 questionnaires were used for statistical analysis. Analysis was performed using Partial Least Squares (PLS SEM). Results indicate that communication, perceived price, perceived product quality significant impact on trust brand, It also the finding shows that trust has a positive significant impact purchase behavior, the constructed model has a good goodness-of-fit index. This study also discusses practical implications and applications for developing and less developed countries.